PENDAMPINGAN PENGGUNAAN TEKNOLOGI KEPADA PELAKU UMKM “MANCEGAR” - Encep Saefullah; Difla Sanaya; Anil Hotimah; Fianto Akbar Nugraha; Rahmadani Rahmadani (Jurnal Abdimas Bina Bangsa, 2023)
The problem that occurs with “Mancegar” UMKM in Pasir Limus Village, Pamarayan District, Serang Regency is that in marketing and production activities they have not used technology so that it affects sales volume, market segmentation and production volume. This service activity aims to provide assistance related to the application of technology in marketing activities and production processes as part of science and technology transfers to maximize their business. As a result of the implementation of this activity, the community's knowledge and understanding of business management has increased, marketing has used e-commerce/marketplaces and product innovations in the form of more diverse flavors and packaging variants as well as the use of tools with a touch of technology in their production